Pengenalan Teknologi Artificial Intellegence Pada Panti Asuhan Al Hidayah Padang - Syahputra, Hadi; Yanto, Musli; Fenia, Selvi Zola (LPPM Universitas Dharma Andalas, 2025)
The rapid development of information technology in the era of the Industrial Revolution 4.0 has had a major impact on various aspects of life, including the world of education and the daily lives of the younger generation. One of the most prominent technologies today is Artificial Intelligence (AI). Understanding of AI is still very limited, especially among teenagers who come from economically disadvantaged backgrounds, including children in orphanages. Children at the AL-Hidayah Padang Orphanage often face limited access to information and cutting-edge technology, including knowledge about AI. As part of the role of the tri dharma of higher education, lecturers have a responsibility to participate in educating the nation's life through community service activities. Through the PKM program entitled